1–Alpha, 25–Dihydroxyvitamin D3 Regresses Endometriotic Implants in Rats by Inhibiting Neovascularization and Altering Regulation of Matrix Metalloproteinase. Issue 1 (January 2014) - Yildirim, Basak; Guler, Tolga; Akbulut, Metin; Oztekin, Ozer; Sariiz, Gulcin
Abstract: Background: The exact pathogenesis of endometriosis has not been completely discerned. 1–alpha, 25–dihydroxyvitamin D3 (1, 25[OH][2]D[3]) has been shown to have an anti–angiogenic effect and extracellular matrix–proteases–degrading properties. We hypothesized that 1, 25(OH)(2)D(3) may have therapeutic value in the treatment of endometriosis.Methods: Endometrial tissue was implanted into the abdominal peritoneum of 21 Wistar albino rats; the rats were randomized into 3 groups. In Group A (simultaneous group), we simultaneously induced endometriosis and began 1, 25(OH)(2)D(3) treatment. Group B rats (sequential group) were treated after endometriosis was documented. Animals in Group C (control group) were followed without any treatment after the development of endometriosis.Results: Histologic score, mean volume, and weight of the explants in Group A and B were found to be significantly lower than those of the control group. Levels of vascular endothelial growth factor (VEGF) and matrix metalloproteinase–9 (MMP–9) immunoreactivities in Group A and B were also significantly lower compared with Group C. In contrast, intensities of immunoreactivity staining for tissue inhibitor of metalloproteinase–2 (TIMP–2) in Group A and B were significantly higher than that of the control group.Conclusion: 1, 25(OH)(2)D(3) regresses endometriotic implants in rat models by altering implant levels of VEGF, TIMP–2, and MMP–9.